Teaching and Promoting Engagement with OSS: Yet Another Experience Report - Flach, Christina Von; Feitosa, Daniela Soares (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
OSS-based learning refers to using open source software (OSS) and their sociotechnical practices in the pedagogical context. Several educators reported its benefits and barriers within different contexts, goals, and areas of knowledge, bringing evidence that it is a feasible approach to address Software Engineering Education challenges. Some appealing factors to adopting OSS-based learning are the availability of the software source code and workflows, access to the OSS community, and information about its development and evolution, which may improve the learning of SE concepts and practices and foster students’ engagement in real-world projects. Observing students as they work towards hard and soft skills, understanding, engaging with, and eventually contributing to an OSS project is a rewarding part of the routine of educators who have recognized the benefits of OSS-based learning and adopted it in their classes. We report our experience after delivering a “hands-on” course to introduce graduate students to OSS projects and their sociotechnical practices. Some graduate students were higher education instructors in other institutions. We present the course design and details of its execution, followed by a reflection based on students’ feedback and our perceptions of gains and pains. Overall, students valued the course and were highly motivated to explore OSS, especially those who worked as educators. Most of the feedback concerning the course methodology was positive, but some students requested more information about the weekly lesson plans in advance. We hope this experience report helps to demystify OSS, inspire educators to adopt OSS projects in their courses, and foster instructors’ and students’ engagement with OSS projects.